The prevalence of thiamine deficiency among elderly nursing home residents: A cross‐sectional study - Nozomu Uchida; Mayumi Ishida; Izumi Sato; Akira Yoshioka; Takao Takahashi; Daisuke Furuya; Yasuhiro Ebihara; Hiroshi Ito; Hideki Onishi (Journal of General and Family Medicine)
Abstract Background Although thiamine deficiency (TD) can lead to Wernicke encephalopathy, the characteristics associated with TD in the elderly have not yet been clarified. We sought to clarify the frequency of TD among an institutionalized elderly population with a controlled dietary intake and to identify possible factors related to TD. Method We undertook a cross‐sectional study of residents in three nursing homes for the elderly as of June 2020. Blood thiamine concentrations were measured using a high‐performance liquid chromatography method, with TD defined as a concentration of <21.3 ng/mL. Basic data (age, sex, height, weight, and BMI), dietary intake for the previous 3 weeks, degree of care (DOC), degree of independence in daily life for elderly with dementia (DIDLED), and comorbidities were analyzed using descriptive statistical methods. Results The mean age (±SD) was 86.9 years (±8.29), with 84 residents (70.0%) being female. The DIDLED varied from total independence to long‐term care level 5 (full assistance), with 89.2% suffering dementia. The mean whole blood thiamine value was 36.18 (±17.58) ng/ml, with TD confirmed in 7 (5.8%) of the 120 residents. All TD patients suffered from dementia. No TD was observed in patients with a near‐normal food intake, and no related factors were observed among the other items. Conclusion Reduced food intake may at increase the risk of TD and symptoms of TD may be overlooked in those displaying symptoms of dementia; thus, it is important for clinicians working with the elderly to remain aware of the potential for TD.